Metformin (1,1-dimethylbiguanide) as potential organic base catalyst for the transesterification of coconut oil with methanol - Vicente, Juvinch R. (University of the Philippines Visayas, 2015)
Biodiesel is conventionally produced by alkali-based trasesterifcation, which is limited by presence of water and free fatty acid content of oil feedstock. This study investigated the potential of Metformin (1,1 -dimethylbiguanide) as an alternative organic base catalyst for the transesterification of coconut oil with methanol. The catalytic of Metformin was compared to that of a common catalyst (sodium hydroxide, NaOH) used in conventional transesterification. When no water was added, Metformin showed significant FAME yield of 55.32 + 7.90% at 1.00% catalyst concentration. Increasing the amount of metformin to 2.00% significantly increased FAME yield to 71.25 + 3.71%. However, NaOH-catalyzed reaction showed significantly higher FAME yield than that of Metformin. In the presence of water(5.0%), the catalytic performance of Metformin was practically lost, with FAME yields of only 5.50 + 0.25% (1.00% Metformin) and 2.61 + 0.43% (2.00% Metformin). Similarly, the presenceof water significantly reduced the catalytic performance of NaOH. Over-all, Metformin showed potential as catalyst for the transesterification of coconut oil with methanol.